2013
DOI: 10.1080/19361521.2013.837567
|View full text |Cite
|
Sign up to set email alerts
|

Five Types of Child Maltreatment and Subsequent Delinquency: Physical Neglect as the Most Significant Predictor

Abstract: Past researchers have often reported that childhood and adolescent maltreatment increases the likelihood of, or is related to, juvenile criminality. However, research examining how specific types of maltreatment (physical abuse, emotional abuse, sexual abuse, physical neglect, emotional neglect) relate to later delinquent offense (violent crime, nonviolent crime, status offending, property offending) is minimal. The aim of this study was to augment and expand upon this scant literature. One hundred and sixty o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 36 publications
1
19
0
4
Order By: Relevance
“…Nikulina, Widom and Czaja (2011) found unique impacts of child neglect and child poverty on adult arrest, PTSD. Evans and Burton (2013) found strong effects for physical neglect and juvenile offending. Our study adds to the growing literature calling for much greater attention to child neglect prevention and intervention (Proctor & Dubowitz, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Nikulina, Widom and Czaja (2011) found unique impacts of child neglect and child poverty on adult arrest, PTSD. Evans and Burton (2013) found strong effects for physical neglect and juvenile offending. Our study adds to the growing literature calling for much greater attention to child neglect prevention and intervention (Proctor & Dubowitz, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…It is worth noting that the broader context of familial/parenting risk in houses with adverse living conditions is likely relevant to the findings of this study. Some scholars have even pointed to certain housing conditions (e.g., health/safety hazards) as potentially indicative of a pattern of child neglect (particularly physical neglect—see Dubowitz, Pitts & Black, ; Fowler et al., ), which itself has been linked to delinquent involvement (Evans & Burton, ). Ancillary analyses accounting for the involvement of Child Protective Services (e.g., being contacted by CPS for suspicion of child abuse/neglect), however, did not alter the findings of this study.…”
Section: Discussionmentioning
confidence: 99%
“…McGee, Wolfe ve Wilson (1997) duygusal istismara uğrayan bireylerin istismar yaşantısı olmayanlara göre daha fazla problem davranışlara yöneldiklerini belirtmiş-lerdir. Evans ve Burton (2013) tarafından duygusal istismarın suça karışma üzerinde önemli bir faktör olduğu bulunmuştur. Arslan (2012) tarafından aile içerisinde istismar algısı arttıkça ergenlerde alkol kullanımı, sigara kullanımı, anti-sosyal davranışlar, intihar eğiliminin arttı-ğı ve beslenme alışkanlıklarının bozulduğu rapor edilmiştir.…”
Section: Introductionunclassified
“…Studies support that emotional maltreatment perceived from parent can cause various problem behaviors such as alcohol use, antisocial behavior, and suicide in adolescence (Arslan & Balkıs, 2014;Holden & Ritchie, 1991;Ireland et al, 2002;Kabasakal & Arslan, 2014;Taşdelen, 1995). Researchers, for example, that emotional maltreatment is associated with delinquency, antisocial behavior, alcohol use, suicide tendency, tobacco use or smoking, and various nutritional problems in adolescents (Arslan, 2012;Bal, 2010;Evans & Burton, 2013;Kabasakal & Arslan, 2014). Research also reported that some personal, family, and social characteristics of individuals can help to cope with risk or adversity successfully, including emotional maltreatment.…”
Section: Extended Summarymentioning
confidence: 99%